Pyrus communis, Common Pear - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
The showy flowers and manageable height of common pear makes it a favorable ornamental landscape tree. Some find the aromatic flowers and sweet edible fruits to be an additional plus; however, a pollinator specimen must be nearby in order for the female tree to produce fruit. Careful consideration should be taken when choosing a planting location, since the soft fruits can be messy if not harvested. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, August 2012.